Kemasan Flexible dan Standing Pouch Ditinjau dari Cemaran Mikroba - Bahar, Imelda; Hendri, Nurfarahim; Novita, Alda (Politeknik ATI Padang, 2020)
Industry Packaging produced the product than package used directly as food or material packaging to protect and secure the products. Therefore, it is necessary to review the presence of microbes that can contaminate the packaging, which can damage food or materials when using the packaging. The presence of contaminating microbes such as mold, Coliform yeast, Coliform and E. coli can come from new packaged products. Thus, the sample packaging is tested using the Colony counting method or Plate counting. by doing a swab on the test sample then dissolved and grown on the media. The medium is in the form of a petri film spreader in accordance with the microbes to be tested and then observed and the growth count is calculated. The microbes observed were Coliform, mold, and yeast as well as E. coli on flexible packaging and Coliform on standing pouch. After conducting the research, there was’n the type of microbe tested or zero and in accordance with the packaging industry company standards.